Ancestral genealogies in modern China - Segawa, Masahisa, 1957- author.
1 online resource.
Keywords: "This book explores the remarkable phenomenon of Chinese lineages - groups of people connected through patrilineal kinship ties, which have existed for centuries in China and which are currently undergoing significant revival after being suppressed in many parts of China during the cultural revolution period. The book considers how lineages and the associated networks and membership associations have developed, surveys how lineages have been studied by anthropologists and others over time in different ways, and discusses the important social functions of lineages in contemporary Hong Kong and mainland China"--